A comprehensive and longitudinal cardiac magnetic resonance imaging study of the impact of coronary ischemia duration on myocardial damage in a highly translatable animal model. (1st September 2022) - Radike, Monika; Sutelman, Pablo; Ben‐Aicha, Soumaya; Gutiérrez, Manuel; Mendieta, Guiomar; Alcover, Sebastià; Casaní, Laura; Arderiu, Gemma; Borrell‐Pages, María; Padró, Teresa; Badimon, Lina; Vilahur, Gemma
Abstract: Objectives: We performed a comprehensive assessment of the effect of myocardial ischemia duration on cardiac structural and functional parameters by serial cardiac magnetic resonance (CMR) and characterized the evolving scar. Background: CMR follow‐up on the cardiac impact of time of ischemia in a closed‐chest animal model of myocardial infarction with human resemblance is missing. Methods: Pigs underwent MI induction by occlusion of the left anterior descending (LAD) coronary artery for 30, 60, 90 or 120 min and then revascularized. Serial CMR was performed on day 3 and day 42 post‐MI. CMR measurements were also run in a sham‐operated group. Cellular and molecular changes were investigated. Results: On day 3, cardiac damage and function were similar in sham and pigs subjected to 30 min of ischemia. Cardiac damage (oedema and necrosis) significantly increased from 60 min onwards. Microvascular obstruction was extensively seen in animals with ≥90 min of ischemia and correlated with cardiac damage. A drop in global systolic function and wall motion of the jeopardized segments was seen in pigs subjected to ≥60 min of ischemia. On day 42, scar size and cardiac dysfunction followed the same pattern in the animals subjected to ≥60 min of ischemia. Adverse left ventricular remodelling (worsening of both LV volumes) was only present in animals subjected to 120 min of ischemia. Cardiac fibrosis, myocyte hypertrophy and vessel rarefaction were similar in the infarcted myocardium of pigs subjected to ≥60 min of ischemia. No changes were observed in the remote myocardium. Conclusion: Sixty‐minute LAD coronary occlusion already induces cardiac structural and functional alterations with longer ischemic time (120 min) causing adverse LV remodelling. Abstract :